Discussing age-related functional decline in family medicine: a qualitative study that explores both patient and physician perceptions. (12th December 2019) - Viret, Ophélie; Schwarz, Joëlle; Senn, Nicolas; Mueller, Yolanda
Abstract: Background: evaluating a patient's functional status and screening for geriatric syndromes by general practitioners (GPs) are increasingly encouraged. This study aimed to explore how older people and GPs define and perceive autonomy and functional decline, patients' propensity to discuss age-related issues and integration of such topics into routine medical consultations. Methods: this qualitative study was conducted in Western Switzerland with older people followed in primary care practices and who participated in a trial assessing the effectiveness of a screening and management tool for geriatric syndromes to prevent functional decline. We interviewed 15 participants (patients ≥75 years old) and five GPs about their screening experience. We used semi-structured grids for data collection and an inductive thematic approach for data analysis. Results: participants gave several definitions of autonomy, directly depending on their health status and functional limitations. Implementing various coping strategies, participants also expressed contrasted feelings related to functional decline such as fear, inability to accept and resilience. Functional decline was often perceived as normal ageing; participants were therefore not prompt at discussing age-related issues with their GP. However, screening was perceived positively by both participants and GPs, making addressing sensitive issues and detecting new problems possible. Conclusions: a geriatric syndrome-screening intervention was well accepted by both patients and physicians. This type of initiative may be an opportunity to address various age-related issues and to inform patients of existing solutions.